2017
DOI: 10.1007/s00406-017-0843-5
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Behavioral Analysis System of Psychotherapy as group psychotherapy for chronically depressed inpatients: a naturalistic multicenter feasibility trial

Abstract: The Cognitive Behavioral Analysis System of Psychotherapy (CBASP) is a relatively new approach in the treatment of chronic depression (CD). Adapted as group psychotherapy for inpatients, CBASP is attracting increasing attention. In this naturalistic multicenter trial, we investigated its feasibility after 10 sessions of CBASP group therapy over a treatment time of at least 5 to a maximum of 10 weeks. Treatment outcome was additionally assessed. Across four centers, 116 inpatients with CD (DSM-IV-TR) attended C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 49 publications
3
16
0
1
Order By: Relevance
“…Results reported by Sabass et al. ( 23 ) for inpatient group CBASP reveal a comparable large effect size ( d =1.11) at posttreatment for 24 sessions of group CBASP using the BDI-II ( 64 ) as is reported for this study sample (eta square=0.18).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Results reported by Sabass et al. ( 23 ) for inpatient group CBASP reveal a comparable large effect size ( d =1.11) at posttreatment for 24 sessions of group CBASP using the BDI-II ( 64 ) as is reported for this study sample (eta square=0.18).…”
Section: Discussionsupporting
confidence: 76%
“…The feasibility of a maximum of 10 sessions of CBASP group therapy adapted for chronically depressed unipolar inpatients was assessed in a large multicenter study by Sabass et al. ( 23 ). The concept of acceptability was measured by self-report questionnaires completed by patients and therapists separately.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, the effect of PMT that was incorporated in the CBASP program is not entirely clear, although we found that effects on depression severity continued after PMT had stopped. It is known that participants in other Group‐CBASP studies have also received other interventions, for example, therapies that are offered on the unit where patients stay while receiving Group‐CBASP (Sabaß et al ., 2018). This limits comparisons between studies and is an important issue to take into account in future Group‐CBASP investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment outcome studies on both types of programmes are scarce. Regarding the inpatient setting, two feasibility studies, of 70 and 116 patients, respectively, indicate that Group‐CBASP is a feasible psychotherapy with promising outcomes for persistently depressed patients (Brakemeier et al ., 2015; Sabaß et al ., 2018). In the few studies conducted on outpatients, Group‐CBASP appeared to be equally effective or even more effective than treatment‐as‐usual (Locke et al ., 2017; Michalak, Schultze, Heidenreich & Schramm, 2015; Negt et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Zudem vermag das intensive stationäre CBASP-Konzept, welches ja speziell auf die Bedürfnisse und Probleme der chronisch depressiven und zuvor als therapieresistent eingestuften Patienten ausgerichtet ist, womöglich diesen Patienten durch den störungsspezifischen maßgeschneiderten Zuschnitt der Strategien auf ihre Probleme zumindest einen ersten Schritt aus der chronischen Depression aufzeigen, sodass sich niemand in der Fremdbeurteilung verschlechterte. Ähnliche positive Ergebnisse zeigt auch eine naturalistische Multicenterstudie, welche die stationäre CBASP-Gruppentherapie untersuchte [41].…”
Section: Diskussionunclassified